Politeness Strategies in Academic English Presentations: A Systematic Literature Review of Teacher – Student Interaction - Lia Mahardika Harahap; Rasyidah, Ummi (Student Scientific Creativity Journal, 2026)
This systematic literature review investigates the realization of language politeness in English learning presentation activities, focusing on teacher-to-student and student-to-student interactions. Employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework, this study synthesized peer-reviewed journal articles published exclusively within the period 2020–2026. A total of 47 initial records were identified through database searches of Google Scholar, ERIC, and Scopus. After applying rigorous inclusion and exclusion criteria including the restriction to publications between 2020 and 2026 twelve journal articles were selected for thematic synthesis. The theoretical anchor is Brown and Levinson’s (1987) politeness model, complemented by contemporary empirical studies on EFL classroom interaction, gender and politeness, pragmatic competence, and technology-mediated communication. The synthesis reveals that teachers predominantly employ negative and positive politeness strategies to maintain authority while fostering rapport, whereas students favor positive politeness in peer interactions but frequently deviate from formal politeness norms in structured presentation contexts. These deviations are attributed to pragmatic competence gaps, power asymmetries, gender, and cultural factors. This review underscores the critical importance of integrating explicit pragmatic instruction into English language teaching, particularly for structured oral presentation activities that demand a high degree of communicative competence.